Fine Arts: 1. Art During the Transition Period Between Paleolithic and Neolithicon the Territory of Romania - Olaru Ioana-Iulia (Sciendo, 2018)
This material refers to one of the many transition periods from the History of Art on the territory of Romania - that is the period which separates Paleolithic from Neolithic: Epi-Paleolithic, with its endcalled (and accepted, first of all!) by some researchers: Mesolithic. As we will see, we will refer to the art of this moment of great complexity and diversity. From an artistic pointof view, Epi-Paleolithic already has tools which can be placed in the category of technical beauty, as far as form is concerned, precision becomes more and more important,and also the skillfulness of their production and the delicate, refined finishing; also connected to the artistic side of the period, the interest for beauty for creating geometrical-abstract decorations increases, obviously becoming a coherent ornamental motif. In the final phase of Epi-Paleolithic, the Mesolithic period comes with an art which is different from the one of the culture Schela Cladovei, characterized by ornaments with simple geometrical motifs, liniar incisions, oblique or in a network, this geometry leading to the main compositional textures of decoration of the oldest phase of the future Neolithic culture Criș.